(2)+(3)=

Simple and best practice solution for (2)+(3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2)+(3)= equation:


Simplifying
(2) + (3) = 0
2 + (3) = 0
2 + 3 = 0

Combine like terms: 2 + 3 = 5
5 = 0

Solving
5 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 24+9x-12x=3x-4x | | 1.5x=2(x-15) | | -0.6+(2.5)= | | 24p+16=32p-48 | | 9x^2-51x=168 | | -8+1=-14+7 | | (2x-2)2-10(2x-2)+21=0 | | X-1=11+5x | | 2y^3-2y^2-6y-10=0 | | 15x-7[x+2]=5x-2 | | X-.33x=25000 | | -68-(-25)= | | N+1=3n+9 | | (xy)dx+(x+1)dy=0 | | 0.95x+0.05(2-x)=0.10(163) | | 4z^2-4x=24 | | 12 = k2 + 10 | | 72x^2-8x+9=0 | | 3.5+(-7.5)= | | -1-6p=6-7p | | n-9-9n=1-7n | | 7=2g+3 | | 6+6n=-4(2-5n) | | 3.5+(7.5)= | | 28-6x=49-9x | | (X+1)=x | | 14y+41=139 | | 0.33333333333(21-3a)=6-a | | 3x+2x-11=84 | | 6x+0.4=6.4 | | -2x-18=-(1-2x)+4x | | 4(a+2)=14-2(3-a) |

Equations solver categories